Effectiveness of Babada Corp's Corporate Social Responsibility (CSR) Program in Pekanbaru City - Utami, Fadilah Rizka; Mashur, Dadang (CV. Rayyan Dwi Bharata, 2024)
The presence of a company within the society is fundamentally anticipated to be beneficial and capable of fostering a mutually symbiotic relationship between the two entities. Each company is obligated to attend to its surrounding environment through Corporate Social Responsibility (CSR) programs or social responsibilities. Many companies overlook the well-being of the society around them and engage in CSR merely as a formality. However, Babada Corp, operating in the food industry, consistently implements CSR programs and internalizes them as a matter of consciousness. This study aims to discover the effectiveness of Babada Corp's Corporate Social Responsibility (CSR) program on the surrounding community and to identify the hindering factors that impede the company in fulfilling its obligations through CSR programs.The methodological approach implemented in this research is qualitative method with descriptive phenomenological approach, using data collection techniques such as observation, interviews, and documentation. The study draws upon Sutrisno's theory of program effectiveness as its theoretical framework. Data for this study consists of primary and secondary data. Primary data obtained through interviews with research informants and secondary data acquired through observations and documentation of the research object.The findings of the study indicate that Babada Corp focuses its CSR efforts on five areas: religious preaching, economic, education, healthcare, and humanity. Despite encountering challenges in implementation, the programs have been effective and sustainable. One of the inhibiting factors is the absence of a predefined schedule due to financial constraints hindering program disbursement.